(untitled) (Journal of Asian Development Studies, 2024)
This research examines the feasibility of green finance initiatives within the financial sector of Pakistan, a country committed to addressing environmental challenges. The study examines the complex relationships between regulatory support, financial institutions’ preparedness, investor sentiments, market dynamics, and the viability of green finance projects. Through a structured questionnaire survey involving professionals from the financial sector, the study unveils critical findings.A supportive regulatory environment positively influences financial institutions’ readiness and fosters positive investor sentiment. Positive investor sentiment, in turn, stimulates the demand for green finance, leading to favorable market conditions. Finally, a conducive market environment enhances the feasibility of green finance initiatives. These findings carry significant implications for policymakers, financial institutions, and investors interested in sustainable finance